2011
DOI: 10.1016/j.gloplacha.2011.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of mean temperature trends in Spain over the period 1961–2006

Abstract: The spatial distribution of recent mean temperature trends over Spain during the period 1961-2006 at monthly, seasonal and annual time scale is carried out in this study by applying various statistical tools to data from 473 weather stations. The magnitude of trends was derived from the slopes of the linear trends using ordinary least-square fitting. The non-parametric Mann-Kendall test was used to determine the statistical significance of trends. Maps of surface temperature trends were generated by applying a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
45
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(59 citation statements)
references
References 75 publications
10
45
0
4
Order By: Relevance
“…When the study is extended to a longer period at land stations, maximum rates are registered in June and also in August with a trend of 0.06 ºC/year for both months. These land temperature results are consistent with those studies which indicate that warming observed in recent decades is mainly due to the increase of temperatures during the warm seasons, either spring or summer (Morales et al, 2005;Brunet et al, 2007;Del Río et al, 2011;Bartolini et al, 2012;El Kenawy et al, 2012). However, our data indicate that the warming takes place precisely during the transition from spring to summer with June being the month when the largest changes have been recorded especially during the last three decades.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…When the study is extended to a longer period at land stations, maximum rates are registered in June and also in August with a trend of 0.06 ºC/year for both months. These land temperature results are consistent with those studies which indicate that warming observed in recent decades is mainly due to the increase of temperatures during the warm seasons, either spring or summer (Morales et al, 2005;Brunet et al, 2007;Del Río et al, 2011;Bartolini et al, 2012;El Kenawy et al, 2012). However, our data indicate that the warming takes place precisely during the transition from spring to summer with June being the month when the largest changes have been recorded especially during the last three decades.…”
Section: Discussionsupporting
confidence: 93%
“…Most studies agree that there has been an increase in temperature from the 1970s onward (Esteban-Parra et al, 1995Serra et al, 2001;Morales et al, 2005;Salat and Pascual, 2006;Brunet et al, 2007;Homar et al, 2010;Del Río et al, 2011;El Kenawy et al;. Amongst them, we highlight those that explore the monthly, seasonal and annual variability of the warming trends.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Missing values in the available data were replaced (Suhaila et al, 2008) by mean monthly values (Muñoz-Díaz and Rodrigo, 2006). These missing data were less than 3% of the total data used in this study (del Río et al, 2011).…”
Section: Data Collectionmentioning
confidence: 99%